Training on Utilizing an IoT-Based Inorganic Waste Management System for Sustainable Public Welfare - Ruli Supriati; Ageng Setiani Rafika; Dwi Andayani; Aulia Rahma Dina; Muhammad Ghifari Ilham; Ersa Aura Natasya; Irene Apriani Widjaya (ADI Publisher, 2025)
The increasing accumulation of unmanaged inorganic waste has become a serious environmental issue that threatens ecosystem sustainability and public health. However, the distribution of advanced technology has not yet reached many local communities. Therefore, the Orange Box technology was introduced as an Internet of Things (IoT)-based innovation designed to automatically sort and recycle inorganic waste through intelligent detection and data-driven processing systems. The intended benefits for the community are to improve the effectiveness and social impact of waste management through the implementation of the Orange Box. Hence, technological literacy and training are required to enhance the efficiency of waste sorting and utilization. This community service program applied a mixed-methods approach, combining surveys, direct observations, and interviews to assess community behavior, awareness levels, and satisfaction. The results of continuous socialization and training activities showed a significant increase in the quantity and accuracy of inorganic waste sorting, as well as improved public awareness of sustainable waste management. Furthermore, the community found the system easy to use and motivating for consistent waste sorting practices. These findings confirm that IoT technology plays an essential role in achieving smart waste management and fostering environmental responsibility at the community level, in alignment with the Sustainable Development Goals (SDG 12 Responsible Consumption and Production, and SDG 13 Climate Action). Future studies are recommended to expand implementation, integrate economic incentives, and enhance real-time monitoring systems for broader urban applications.